Description of five new species of Heliura Butler (Lepidoptera: Erebidae: Arctiinae: Arctiini: Ctenuchina), with discussion on H. pierus (Cramer) and the H. stolli (Rothschild) species group. Issue 4 (17th February 2016) - Pinheiro, Lívia R.; Cerda, Jean-Aimé; Duarte, Marcelo
Abstract: Fivenew species of Heliura Butler (Lepidoptera: Erebidae) are described: H. laguerrei Pinheiro and Cerda, H. beneluzi Pinheiro and Cerda, Heliura crameri Pinheiro and Cerda, H. nigriventris Pinheiro and Duarte, and H. pauloi Pinheiro and Duarte. The last three species are placed in the H. stolli (Rothschild) species group, which is delimited for the first time and discussed. The other known species that are also part of this group are redescribed, and an identification key is provided. Heliura pieroides Rothschild is a revalidated combination. Heliura parcipuncta is a new combination. Heliura pierus Cramer is considered a species inquirenda . Illustrations of habitus and genitalia of the species treated herein are provided whenever possible.